MENINGKATKAN HASIL BELAJAR PKN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT PADA SISWA KELAS V SD NEGERI 007 KELAYANG KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Wirdanis Wirdanis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The background of the researcher conducted this study because the researchers found the learning system in SD Negeri 007 Kelayang still using conventional methods that make students bored and not active in learning. This happens because students are not given the opportunity to appreciate their knowledge. Students just shut up, sit down, and record what the teacher taught. Therefore, the teacher can use various learning concepts to improve the quality of the learning. Researchers, as well as teachers, use the NHT type of cooperative learning method to improve student learning outcomes and also make teachers know how to teach well. This classroom action research aims to improve the learning process and solve the problems the teacher gets in the classroom. Data obtained after research on teacher activities in the first cycle of the 1st meeting were 55%, the second meeting with 68%, in the second cycle the third meeting was 84%, and at the 4th meeting, the percentage was obtained 93%. Student observation data in this study obtained the percentage of the first cycle of the first meeting of 50%, the second meeting of 57%, in the second cycle of the third meeting was 79%, and the fourth meeting obtained a percentage of 88%. This proves that student activity has increased. Data on the increase in student learning outcomes in grade 1 SDN 007 Kelayang, Rakit Kulim Subdistrict in the initial data obtained an average of 62, in the first daily test obtained a class average of 81, and the daily test II obtained an average of 86. This proves that the use of the STAD cooperative learning method is effectively used in class V.